Origines historiques de l'injonction en droit québécois - Prujiner, Alain (Les Cahiers de droit, 1979)
This survey of the historical origins of injunction in Quebec law aims at elucidating the source of some of the difficulties that have arisen lately in this much-debated field. In fact, the presence of injunction in Quebec procedural law results from specific circumstances. The need for such a procedure came from the continuation of the old French law of civil procedure after the conquest of Canada by Britain. At that time, adequate proceedings for cases of urgency had not yet been devised and did not appear in the Ordonnance of 1667, which remained in force in Quebec up to 1867. From 1763, English influence became predominant, through legislation aimed at altering this corpus of French law to adapt it to the new judicature inspired by the English system. Nevertheless, in the absence of equity jurisdiction, no serious attempt to introduce injunction was made prior to the codification. Even the first Code of Civil Procedure of 1867 did not provide for injunctions, though their need became obvious. In spite of urgings by commentators, and the existence of provisions in the Louisiana Code, the Legislature declined to adopt injunction. Courts then assumed authority to grant injunctions, either under their inherent powers or from a broad interpretation of mandamus. However, in Carter v. Breakey, Meredith C.J., for the Superior Court, after very detailed consideration of the issue, firmly opposed such endeavours as dangerous and unlawful, while urging the Legislature to make provision for the issuing of injunctions in appropriate cases. An Act was finally passed to this end in 1878. This early provision cautiously restricted the use of injunctions to six types of cases. Subsequent developments, however, especially in the new codes of 1894 and 1966, considerably broadened its scope. Adapting an equitable remedy to the general scheme of Quebec procedural law was a difficult process, producing much uncertainty in the case-law. Further, in the absence of other guidance, courts tended to look to English and American sources, thus introducing into Quebec law some principles of equity. The case of injunction in Quebec law therefore seems to illustrate the perils of receiving foreign legal institutions without adequate preparation.